Revisiting the absolute chirality and polymorphism of (–)‐Istanbulin A. Issue 9 (28th August 2020) - Arancibia, Luz; Naspi, Mariana; Pucci, Graciela; Rodriguez, Maricel; Di Salvo, Florencia
Abstract : The natural product (−)‐Istanbulin A was isolated from Senecio filaginoides DC and the chirality is described as 4 S, 5 R, 8 R, 10 S based on single‐crystal X‐ray diffraction studies. (−)‐Istanbulin A corresponds to a polymorph of a previously reported form of (−)‐Istanbulin A (form I) and this is the first time that polymorphism has been reported in the Istanbulin family. Abstract : The terpenoid (−)‐Istanbulin A is a natural product isolated from Senecio filaginoides DC, one of the 270 species of Senecio (Asteraceae) which occurs in Argentina. The structure and absolute configuration of this compound [9a‐hydroxy‐3, 4a, 5‐trimethyl‐4a, 6, 7, 8a, 9, 9a‐hexahydro‐4 H, 5 H ‐naphtho[2, 3‐ b ]‐furan‐2, 8‐dione or (4 S, 5 R, 8 R, 10 S )‐1‐oxo‐8β‐hydroxy‐10β H ‐eremophil‐7(11)‐en‐12, 8β‐olide, C15 H20 O4 ] were determined by single‐crystal X‐ray diffraction studies. It proved to be a sesquiterpene lactone showing an eremophilanolide skeleton whose chirality is described as 4 S, 5 R, 8 R, 10 S . Structural results were also in agreement with the one‐ and two‐dimensional (1D and 2D) NMR and HR–ESI–MS data, and other complementary spectroscopic information. In addition, (−)‐Istanbulin A is a polymorph of the previously reported form of (−)‐Istanbulin A, form I; thus, the title compound is denoted form II or polymorph II. Structural data and a literature search allowed the chirality of Istanbulin A to be revisited. The antimicrobial and antifungal activities of (−)‐Istanbulin A, form II, were evaluated in order to establish a reference for future comparisons and applications related to specific crystal forms of Istanbulins.